ANALISIS TEKNIS DAN FINANSIAL AGROINDUSTRI SKALA KECIL PADA BERBAGAI PROSES PEMBUATAN KERIPIK TALAS DI KABUPATEN LAMPUNG BARAT - Ermayuli Ermayuli; Hanung Ismono; Sri Setyani (Jurnal Teknologi & Industri Hasil Pertanian, 2011)
Taro (Xanthosoma spp.) is widely grown in  West Lampung  area.  The average productivity one 40 ton per hectare per year. The best technique to process taro crisp on a small scale in West Lampung regency, based on consumer preference, was Tiga Putra. If  based on the yield, Kelompok Maju Tani was found the best, in addition , the traditional method was found more efficient if compared to semi-modern method. The analysis of financial showed that   small scale talas crisp industry at  West Lampung regency was considered  to be feasible both processed using  traditional and  semi-modern methods.  This was based on the fact that all criteria required  for financial aspects met with positive results NPV, IRR resulting discount factor is greater than the bank discount factor, Pay back period (PP) is faster than the set time (10 years), and the Net B / C greater than 1 (one).